Negotiating Continuity and Change: Social Capital and Value-Mediated Governance Adaptation in an Indonesian Pesantren - Filda Inayah; Muh. Hanif (Journal of Educational Research and Practice, 2026)
Traditional Indonesian pesantren face the challenge of responding to changing educational, technological, and administrative expectations while maintaining religious and cultural commitments. Although previous research has examined pesantren modernization and leadership, little is known about how relational resources and institutional values interact in everyday governance adaptation. This study examines how social capital and institutional values shaped governance adaptation at Pondok Pesantren Mathali’ul Falah Pekiringan, Central Java, Indonesia. A qualitative single-case design was used, drawing on semi-structured interviews with 12 internal and external stakeholders, 17 participant-observation sessions, and the analysis of institutional documents. Data were analyzed thematically using trust, networks, and norms as sensitizing concepts. Four interrelated findings were identified. Trust in the kiai supports institutional legitimacy but operates alongside parental considerations of affordability, distance, facilities, and educational quality. Alumni and community relationships provide informal, largely voluntary support. Technology was accepted for supervised learning, while personal smartphone use was restricted according to disciplinary and moral priorities. Centralized, family based governance supported continuity but left alumni coordination, documentation, and succession arrangements relatively informal. The findings suggest that relational governance may benefit from gradual, culturally feasible improvements in communication, alumni coordination, supervised digital access, administrative documentation, and leadership continuity. The originality of this study lies in connecting social capital with value-mediated governance adaptation to explain how change may be selectively accepted, limited, or reorganized within a culturally embedded educational institution. This case-based perspective is intended as an analytical heuristic rather than a general model for all pesantrens.